Risiko Ergonomi pada Postur Tubuh Operator Produksi Pengemasan Aluminium Sulfat Padat - Fanegi, Clara Nisa; Hendra, Hendra (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
One important aspect of ergonomics is the analysis of work posture, which examines how body position during work can affect health outcomes. This study aimed to analyze the work posture of solid aluminum sulfate packaging production operators at PT. XYZ. This study was a descriptive study involving solid aluminum sulfate packaging production operators at PT XYZ. The operator's work posture was observed directly and video recording of the operator's activities during the packaging process was carried out. Work posture was assessed using the Rapid Entire Body Assessment (REBA) method to assess ergonomic risks that have the potential to cause musculoskeletal disorders, so that they can be analyzed descriptively. The results showed that activities in the packaging process, such as moving products from the bagging hopper to the scale and moving products after the stripping process onto the pallet, had very high REBA scores, indicating a significant risk for musculoskeletal disorders. Unergonomic work postures, such as bending at excessive angles and rotations, were found to be the main factors that increase the load on muscles and joints, thereby increasing the likelihood of injury. It was concluded that many packaging operator work postures are at high risk for musculoskeletal disorders.Keywords: aluminum sulfate packaging; operator; posture; ergonomics; musculoskeletal disorders  ABSTRAK Salah satu aspek penting ergonomi adalah analisis postur kerja, yang meneliti bagaimana posisi tubuh selama bekerja dapat memengaruhi hasil kesehatan. Penelitian ini bertujuan untuk menganalisis postur kerja operator produksi pengemasan aluminium sulfat padat di PT. XYZ. Penelitian ini merupakan studi deskriptif yang melibatkan para operator produksi pengemasan aluminium sulfat padat di PT XYZ. Postur kerja operator diobservasi secara langsung dan dilakukan perekaman video aktivitas operator selama proses pengemasan. Postur kerjadi dinilai menggunakan metode Rapid Entire Body Assessment (REBA) guna menilai risiko ergonomi yang berpotensi menyebabkan gangguan muskuloskeletal, agar bisa dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa aktivitas dalam proses pengemasan, seperti pemindahan produk dari baging hopper ke timbangan dan pemindahan produk setelah proses stripping ke atas pallet, memiliki skor REBA yang sangat tinggi, yang menunjukkan risiko signifikan untuk terjadinya gangguan muskuloskeletal. Postur kerja yang tidak ergonomi, seperti membungkuk dengan sudut dan rotasi yang berlebihan, ditemukan sebagai faktor utama yang meningkatkan beban pada otot dan sendi, sehingga memperbesar kemungkinan terjadinya cedera. Disimpulkan bahwa banyak postur kerja operator pengemasan yang berisiko tinggi untuk terjadi gangguan muskuloskeletal.Kata kunci: pengemasan aluminium sulfat; operator; postur; ergonomi; gangguan muskuloskeletal